Peran Faktor-Faktor Keuangan Dan Pertumbuhan Ekonomi terhadap Penerimaan Pendapatan Asli Daerah - Pratolo, Suryo; Yudha, Binang Sukma (Journal of Accounting and Investment, 2011)
The objective of the study is to empirically examine the role of finacial factors ad economic growth to acceptance of regional own revenue. The samples of study are direct revenue, economic growth, and acceptance of regional own revenue in 2007–2009 at 391 municipal. The empirical results show that the employee expenditure has negative and significant directly effect to economic growth. While good and service expenditure has positive and significan on directly effect to economic growth. Capital expenditure has positive and not significan on directly effect to economic growth. While the employee expenditure has positive and significant on indirectly effect to acceptance of regional own revenue by means of economic growth. Good and service expenditure has positive and significant on indirectly effect to acceptance of regional own revenue by means of economic growth. Capital expenditure has positive and not significan on indirectly effect to acceptance of regional own revenue by means of economic growth. While directly effect of the economic growth to acceptance of regional own revenue are positve and not significant.